(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Contributo sottoposto a valutazione SOMMARIO: 1. Il principio di collaborazione tra autorità civili e religiose - 2. Lo sviluppo delle intese sul piano regionale - 3. Gli accordi regionali vigenti – 4. L’attuale quadro normativo: il doppio livello centro-periferia – 5. Il coinvolgimento degli organi periferici del Ministero - 6. Le ulteriori prospettive di un sistema complesso - 7. Conclusioni. The cultural goods of religious interest between national agreement and ("old" and "new") regional agreements Abstract: The Agreement of 1984 deals with the relations between Catholic Church and State regarding cultural heritage in Italy (Article 12). This law gives rise to a complex and articulated system, because essentially based on two-tier “center-periphery”. This dual implementation plan deserves some insights in the light of the reforms that have involved the field of cultural heritage in general and the organization of the Ministry (MiBAC). Also be studied some recent and significant changes in the applications of such laws that appear indicative of the process of collaboration in action. Keywords: Cultural Heritage, Catholic Church, Cooperation, State-Church Relations